Safe Drinking Water in Kuna Yala: Field Notes from Panama - Halperin, Michael (Consilience, 2008)
Starting in early 2003, Michael Halperin worked for two years as a Peace Corps volunteer in the indigenous Kuna island community of Ustupu, just off the Northeastern coast of Panama. His workfocusedontheissueofpotablewateranddiarrhealdisease. Thesefieldnotesfocusonthe implementation of sustainable technologies and practices for clean water. Emphasized is the importance of local knowledge, partnerships, and indigenous leadership. This story chronicles a two-year process of considering, rejecting, and finally developing the most workable solution for safe water: solar water purification. Unlike boiling and chlorination, this method was acceptable to the Kuna because it does not conflict with cultural practices on the island. It is likely that this method of water purification can be sustained over time.